Prediction of Academic Motivation Based on Learning Strategies, Self-Efficacy Perception, Self-Esteem, Self-Regulation, Psychological Capital, and Academic Achievement Among Students of Dhi Qar University - Zaben khawwaf , Zaman; Mahdad, Ali; Salman Gatfan , Muntadher; Farhadi , Hadi (KMAN Counseling & Psychology Nexus, 2024)
The aim of this study was to predict academic performance based on academic motivation, learning strategies, self-efficacy perception, self-esteem, self-regulation, psychological capital, and academic achievement among students. The statistical population consisted of all male and female students at Dhi Qar University in 2024. From this population, 300 students (150 females and 150 males) were selected using a multistage cluster sampling method. Data were collected using the following questionnaires: learning strategies (Karami et al., 2005), academic self-efficacy (Onwuegbuzie & Frels, 1988), self-esteem (Rosenberg, 1965), self-regulation (Boufard, 1995), psychological capital (Luthans & Youssef, 2007), academic achievement (Pham & Taylor, 1999), and academic motivation (Harter, 1981). The data were analyzed using Pearson correlation coefficient and stepwise regression. The findings showed that there was a significant positive relationship between all study variables and academic motivation (p < 0.001). Additionally, the regression analysis results indicated that self-efficacy perception, psychological capital, self-esteem, emotional self-regulation, and academic achievement accounted for 78% of the variance in academic motivation. Therefore, identifying factors such as self-efficacy perception, psychological capital, self-esteem, and emotional self-regulation in relation to academic motivation can improve educational planning, enhance teaching effectiveness, and lead to better academic progress.